Is It Okay to Study Entrepreneurial Orientation (EO) at the Individual Level? Yes! - Clark, Daniel R.; Pidduck, Robert J.; Lumpkin, G. T.; Covin, Jeffrey G. (Entrepreneurship Theory and Practice, 2024)
Entrepreneurial orientation (EO) is an important construct in the fields of management and entrepreneurship research. Interest in EO knowledge continues to thrive with a burgeoning research agenda in multiple contexts and with diverse implications. However, a subset of this research, which endeavors to apply the EO construct to explain or predict individuals’ entrepreneurial beliefs and behaviors, has met with resistance. This paper examines the case for EO at the individual level (Ind.EO). We consider the EO legacy concerns, and the various theoretical implications and benefits of doing so. Drawing upon an “EO as a family of constructs” framework, we propose paths forward for studying Ind.EO credibly, consistent with, but distinct from, traditional firm-level EO. Finally, we outline a research agenda and discuss the contributions and potential implications for Ind.EO research across the wider entrepreneurship discipline.